2022
DOI: 10.1186/s13011-021-00424-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from the medication assisted treatment pilot program for adults with opioid use disorders in rural Colorado

Abstract: Background As Colorado ranked among the top nationally in non-medical use of opioids, a pilot medication for opioid use disorder (MOUD) program was developed to increase the number of NPs and PAs providing MOUD in order to bring this evidence- based treatment to 2 counties showing disproportionally high opioid overdose deaths. Over the first 18 months, the MOUD Pilot Program led to 15 new health care providers receiving MOUD waiver training and 1005 patients receiving MOUD from the 3 participat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…MOUD‐related stigma is well documented in the literature (Amura et al, 2022; Cioe et al, 2020; Garrett & Young, 2022; Kennedy‐Hendricks et al, 2017). Findings from this study revealed participants continue to experience stigmatizing behaviors from healthcare professionals, family, and community members about MOUD.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…MOUD‐related stigma is well documented in the literature (Amura et al, 2022; Cioe et al, 2020; Garrett & Young, 2022; Kennedy‐Hendricks et al, 2017). Findings from this study revealed participants continue to experience stigmatizing behaviors from healthcare professionals, family, and community members about MOUD.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings were consistent with Cioe et al (2020); participants expressed concern with the need to take MOUD because of the perception that it was replacing one drug with another, fear of being seen at a MOUD clinic, and being judged from others in the recovery community. MOUD is considered the most effective treatment for OUD, but stigmatizing attitudes negatively affect retention and adherence to the treatment regimen (Amura et al, 2022; Cioe et al, 2020; Hawk et al, 2021). Amura et al (2022) found withdrawal and detox treatment modalities were favored by some people over MOUD regardless of the known detrimental effects of these inferior treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two counties did not have operational jails at the time of the study, while the other counties have jails with potential to engage with a network of community health clinics and hospitals participating in the Colorado MOUD expansion program under Colorado’s Behavioral Health Recovery Act of 2021 (Senate Bills 19 − 001 and 21–137) (Amura et al, 2023 ). This scale-up program was implemented after the success of the pilot implementation in two Colorado counties with high opioid overdose death rates (Amura, 2022 ). At the time of the study, the seven jails were not part of the larger MOUD expansion efforts.…”
Section: Methodsmentioning
confidence: 99%